Establishment, Characterisation And Mirna Transcriptome Profiling Of Spheroid-Enriched Cells With Breast Cancer Stem Cell Properties - Boo, Lily (2020)
Cancer stem cells (CSCs) are self-renewing cancer cells and are thought to be a source of tumour recurrence. The CSCs population could be enriched in serum-free culture condition as this environment favoured their expansion while the rest of non-CSCs population undergo anoikis. MCF-7 cells, which being the luminal type are non-metastatic, and MDA-MD-231 cells, which are negative for the three breast receptors and regarded as highly aggressive were used in this study. MicroRNAs (miRNAs) regulate both normal stem cells and CSCs, and deregulation of miRNAs has an important role of tumorigenesis. Although there are already some miRNAs that have been reported in breast cancer, precise information on miRNAs involved in breast CSCs is still lacking. Therefore, we sought to evaluate the phenotypic characteristics of the spheroid-enriched cells for their CSCs properties and also to determine the miRNA expression profile. We confirmed the enrichment of the spheroidenriched cancer stem cells-like from human breast cancer cell lines, MCF-7 and MDA-MB-231 by evaluating the characteristics of the in vitro spheroidenriched cells. After obtaining the spheroid-enriched cells, miRNA next generation sequencing and real-time polymerase chain reaction were performed to evaluate their miRNA profile. Our results showed that the spheroid cells iii derived from both breast cancer cell lines were enriched with CSCs properties namely self-renewability, expression of stem cells-related markers, and enhancement of drug resistance. Using a 2-fold expression as the cut-off point, 25 up-regulated and 97 down-regulated differentially expressed miRNAs were identified in MCF-7 spheroid cells compared to their parental cells. On the other hand, 30 up-regulated and 36 down-regulated differentially expressed miRNAs were found in MDA-MB-231 spheroid in relative to the parental cells. The targeted genes from the uniquely deregulated miRNAs found in MCF-7 spheroid cells were enriched in pathways involved in induction of epithelial-mesenchymal transition (EMT) responsible for enhancing invasion and migration of the cells. On the other hand, the targeted genes from the uniquely deregulated miRNAs found in MDA-MB-231 spheroid cells were enriched in pathways involved in maintaining EMT associated with the increased chemoresistance. A total of 20 miRNAs including miR-15b, miR34a, miR-148a, miR-196b, and miR-628 were found to be commonly deregulated between these two breast cancer spheroid-enriched CSCs cell types, which highlights the involvement of these miRNAs in maintaining the CSCs features. The enriched genes were involved in core pathways found in stem cells primarily on focal adhesion, MAPK, Wnt, Hedhehog, mTOR and VEGF. The levels of the selected miRNAs measured by real-time PCR and NGS showed similar trend, indicating the reliability of the sequencing data and supporting the interpretation of the expression profiles and pathways information based on the miRNAs expression results in this study. We have demonstrated that the spheroid culturing method can be used to enrich for CSCs-like subpopulations in both breast cancer cell lines as shown in the iv present study. Our data suggest that there were distinct miRNA expression profiles in spheroid relative to parental cells for both breast cancer cell lines. This reflects that the phenotypic behaviour and other distinctive features of spheroid-enriched CSCs in MCF-7 and MDA-MB-231 are regulated by miRNAs. Further studies are needed to validate whether the panel of these distinct miRNAs could be used as potential molecular targets for clinical applications of breast cancer stem cells.